Gas chromatography and mass spectrometry : a practical guide - Sparkman, O. David (Orrin David), 1942- (Academic Press, 2011)
Gas Chromatography and Mass Spectrometry: A Practical Guide is the second edition to the highly successful book of the same name, originally written by F.G. Kitson, B.S. Larsen, and C.N. McEwen (1996). Designed as a valuable resource to the GC/MS user, this book provides serves as a one-stop-shop covering updated practical instruction necessary for the successful operation of GC/MS equipment. Includes separation conditions for numerous compound types, instruction on how to interpret mass spectral data, extensive correlations of ion masses and neutral losses with possible structures, together w.